PENERAPAN SISTEM MANAJEMEN ISO 9001:2008 TERHADAP KINERJA DOSEN POLTEKKES KEMENKES BENGKULU - Sutriyanti, Yanti (JURNAL MEDIA KESEHATAN, 2014)
ISO and total quality Management is an approach in organization that have focussing to quality and based on participation of human resources, in order to have successation long term by consumen satisfaction . The application of SMM-ISO 9001-2008 have been done since 2012, so it´s easy to chek all of units that not yet have standarisation. Observed of lecturer performant (Tri Darma Perguruan Tinggi) still pound that unclearly documentation that planned with job fungtion that done by lecturer.This research is analized application of management system ISO 9001:2008 for lecturer performant at Poltekkes Kemenkes Bengkulu 2013. This a dysriptive analytic research with crossectional design. Respondens are lecturer at Poltekkes Kemenkes Bengkulu 43 persons. Data analized with chi square and logistic regression test. Result of research indicated that there ara a relationship among training, awareness/care, and lecturer competences with lecturer performant (P<0.05), there are not a relationship between infrastructure and environmental situation with lecturer perpormant in other side, the must influence factorsfor lecturer performant are infrastructure and environmental situasion (change OR more than 10%) after controlled by gender, age, and long of work. Improved continuously of lecture performant standarisation, in or out of campus environment, for doing the research and community development.